2016
DOI: 10.3847/0004-637x/826/1/32
|View full text |Cite
|
Sign up to set email alerts
|

Star Cluster Formation and Destruction in the Merging Galaxy NGC 3256

Abstract: We use the Advanced Camera for Surveys on the Hubble Space Telescope to study the rich population of young massive star clusters in the main body of NGC 3256, a merging pair of galaxies with a high star formation rate (SFR) and SFR per unit area (Σ SFR ). These clusters have luminosity and mass functions that follow power laws, dN/dL ∝ L α with α = −2.23 ± 0.07, and dN/dM ∝ M β with β = −1.86 ± 0.34 for τ < 10 Myr clusters, similar to those found in more quiescent galaxies. The age distribution can be describe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
31
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 42 publications
4
31
1
Order By: Relevance
“…We now see from equation (10) that Γ S (τ 1 , τ 2 ) is simply the integral of M ×(CMF/SFR) over all M . In our previous work, we found that CMF/SFR is nearly the same for the 8 galaxies we analyze in the present work (CFW15, Mulia et al 2016). Thus, we expect to find that Γ S (τ 1 , τ 2 ) is also similar for these 8 galaxies.…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…We now see from equation (10) that Γ S (τ 1 , τ 2 ) is simply the integral of M ×(CMF/SFR) over all M . In our previous work, we found that CMF/SFR is nearly the same for the 8 galaxies we analyze in the present work (CFW15, Mulia et al 2016). Thus, we expect to find that Γ S (τ 1 , τ 2 ) is also similar for these 8 galaxies.…”
Section: Introductionsupporting
confidence: 71%
“…Our results, however, contradict many previous claims that the fraction of stars in bound clusters increases strongly with Σ SF R and Σ H 2 . We find that the previously reported trends are largely driven by comparisons that mixed Γ F ≈ Γ S (0, 10) and Γ S (10, 100), where Γ S (0, 10) was systematically used for galaxies with higher Σ SF R and Σ H 2 , and Γ S (10, 100) for galaxies with lower Σ SF R and Σ H 2 .We showed recently that the mass functions of young clusters (with ages τ < 10 7 yr), when divided by the star formation rate (SFR), are also similar among different galaxies (Chandar et al 2015, hereafter CFW15;Mulia et al 2016). In our sample of 8 galaxies, the amplitude of the cluster mass function (CMF) and the SFR vary by factors ∼ 10 3 , while their ratio (CMF/SFR) varies by less than a factor of two.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While it is possible that the cluster mass functions for the most distant galaxies in our sample may suffer from biases related to crowding, previous works have found the shapes of these distributions to be fairly stable out to the distances of ≈ 40 Mpc. Randriamanakoto et al (2013) and Mulia et al (2016) tested the impact of 'distance bias' by degrading images of galaxies to simulate distances similar to the two most distant galaxies used here, and found the resulting power-law index of the mass function does not differ by more than ≈ 0.2.…”
Section: Previous Catalogs and Mass Functionsmentioning
confidence: 99%
“…We re-examine the mass functions of the cluster population in eight galaxies from our previous studies (Chandar et al 2015(Chandar et al , 2017. The selection and photometry of clusters is based on U BV IHα images taken with the Hubble Space Telescope (HST ) for NGC 4214 (Chandar et al 2017), NGC 4449 (Rangelov et al 2011), M83 (Whitmore et al in prep), M51 , the Antennae , and NGC 3256 (Mulia et al 2016), and U BV R images taken with the Michigan Curtis Schmidt telescope for the LMC and SMC (Hunter et al 2003). Clusters were selected to be compact, but no attempt was made to distinguish bound from unbound clusters based on their appearance.…”
Section: Cluster Mass Functionsmentioning
confidence: 99%